SYNERGY BETWEEN LiDAR AND IMAGE DATA IN CONTEXT OF BUILDING EXTRACTION - Dal Poz, A. P. [UNESP]; Toth, C.; Holm, T.; Jutzi, B. (Copernicus Gesellschaft Mbh, 2014)
This paper compares the paradigms of LiDAR and aerophotogrammetry in the context of building extraction and briefly discusses a photogrammetric strategy for refining building roof polyhedrons previously extracted from LiDAR data. In general, empirical and theoretical studies have confirmed that LiDAR-based methodologies are more suitable in extracting planar roof faces and ridges of the roof, whereas the aerophotogrammetry are more suitable in extracting building roof outlines. In order to exemplify how to explore these properties, it is presented a photogrammetric method for refining 3D building roof contours extracted from airborne LiDAR data. Examples of application are provided for this refining approach.
Keywords: Aerophotogrammetry; LiDAR; Building extraction